2022
DOI: 10.1177/0021955x221088392
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the mechanical and acoustical properties of flexible polyurethane foam/waste seashell composites for industrial applications

Abstract: The importance of this work is the use of waste seashells WSS (5, 10, 15, 20, 25, and 30 wt.%) as a bio-filler to enhance the mechanical and acoustical characteristics of flexible polyurethane foam (FPU). Petroleum-based polyol was partially replaced by 25% castor oil resulting in high renewable content. The WSS was characterized by X-ray photoelectron spectroscopy (XPS). The chemical structure and morphological features for castor oil-based flexible polyurethane waste seashells (CO-FPU-WSS) composites were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Figure b shows the FTIR spectra of FPU/HNC composites. The signal at 3300 cm –1 , which corresponded to the stretching vibrations of N–H groups, showed that the urethane linkages were successfully created. , The stretching vibrations of the C–H bonds in CH 2 groups were represented by the absorption at 2970 and 2870 cm –1 . , The very low-intensity band at 2275 cm –1 corresponded to unreacted isocyanate . The characteristic bands at around 1720 and 1640 cm –1 were associated with carbonyl groups (C=O) of urethane and monodentate H-bonds of C=O of urea groups, respectively. , Furthermore, the bands at 1593 and 1090 cm –1 indicated the aromatic groups in the examined materials and the stretching vibration of C–O–C for SS, respectively …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure b shows the FTIR spectra of FPU/HNC composites. The signal at 3300 cm –1 , which corresponded to the stretching vibrations of N–H groups, showed that the urethane linkages were successfully created. , The stretching vibrations of the C–H bonds in CH 2 groups were represented by the absorption at 2970 and 2870 cm –1 . , The very low-intensity band at 2275 cm –1 corresponded to unreacted isocyanate . The characteristic bands at around 1720 and 1640 cm –1 were associated with carbonyl groups (C=O) of urethane and monodentate H-bonds of C=O of urea groups, respectively. , Furthermore, the bands at 1593 and 1090 cm –1 indicated the aromatic groups in the examined materials and the stretching vibration of C–O–C for SS, respectively …”
Section: Resultsmentioning
confidence: 98%
“…The signal at 3300 cm −1 , which corresponded to the stretching vibrations of N−H groups, showed that the urethane linkages were successfully created. 37,38 The stretching vibrations of the C−H bonds in CH 2 groups were represented by the absorption at 2970 and 2870 cm −1 . 39,40 The very lowintensity band at 2275 cm −1 corresponded to unreacted isocyanate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control process in both mechanics and acoustics covers large categories ranging from active to passive systems. 13 The passive control systems exploit linear or nonlinear properties of some coupled oscillators or resonators for triggering vibratory/acoustical energies of principal systems and media. As some representative examples of passive systems in mechanics we can name Frahm devices 4 (for linear) and nonlinear energy sink 5 (for nonlinear).…”
Section: Introductionmentioning
confidence: 99%
“…Such nanocomposite materials reinforced with 20 wt% MMTs yielded a smaller water contact angle of 57° when compared with neat fibrous PU with a contact angle of 117°, along with high water flux and oil rejection, and they are thus able to meet the requirement of antifouling membranes used for waste-water treatment [ 14 ]. Maamoun et al [ 15 ] utilised HNTs to promote the sound absorption capability of PU. With the embedding of 1 wt% HNTs, the sound absorption coefficient of nanocomposite materials was improved, as evidenced by the typical shift from a high-frequency to mid-frequency range, as opposed to unfilled PU.…”
Section: Introductionmentioning
confidence: 99%